Penilaian Autentik Berbasis Video Pendek dalam Mengukur Kompetensi Afektif pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Lilik Qonitah; Muhlisin; Rahmi Anekasari (Jurnal Ragam Pengabdian, 2026)
Assessment in Islamic Religious Education (PAI) at the elementary level remains largely focused on written examinations that prioritize cognitive achievement, while affective competence is insufficiently evaluated because direct observation is limited and conventional assessment tends to be subjective. Previous studies have mostly treated video as a learning medium rather than an authentic assessment instrument. Therefore, this study analyzes the implementation of short video-based authentic assessment to measure students’ affective competence in Islamic Religious Education learning. The study used a mixed-methods sequential explanatory design involving 30 sixth-grade students at an elementary school in Batang Regency, Central Java, Indonesia. Data were collected through observation, video assessment, semi-structured interviews, and documentation using an affective rubric covering empathy, apologizing awareness, sincerity in forgiving, self-reflection, and authenticity of expression. The findings showed an average affective competence score of 13.95 out of 20, categorized as good. Authenticity of expression achieved the highest score, whereas self-reflection received the lowest. Overall, short video-based assessment provided more contextual, flexible, and objective evaluation than conventional methods while increasing student engagement and strengthening authentic assessment practices through digital technology integration. The approach also encouraged reflective learning, emotional expression, and meaningful participation during Islamic Religious Education activities among elementary students